Cross-scale interactions of socio-hydrological subsystems: examining the frontier of common pool resource governance in Arizona. (23rd December 2019) - York, Abigail M; Sullivan, Abigail; Bausch, Julia C
Abstract: A critical frontier of water management in the western US is the challenge of cross-scale interactions. It is difficult to establish clear governance boundaries and collectively act when basins are interconnected, surface water and groundwater flows are interrelated, and urban and rural water demands are increasingly affected by regional and international telecoupling. Changing climate, snowpack, and rainfall, peri-urbanization, and shifting economics of rural landscapes further increase sustainable governance challenges. Using a lens of cross-scale interactions drawn from the social-ecological literature, we develop a set of conceptual frames for socio-hydrology that highlight: (1) spatial and temporal mismatches, (2) telecoupled flows, and (3) networked and nested systems. Using the exemplary case of Central Arizona, we explore nesting of the system within the larger western socio-hydrological system (SHS), impacts of changing Colorado River policies, such as the Drought Contingency Plan, and emerging institutional arrangements between the State of Arizona, agricultural communities, and Tribal Nations. We conclude with a set of questions that inform analyses of cross-scale, multi-level governance within social-ecological systems. Without grappling with the dynamics and interconnectedness of SHSs, we cannot sustainably manage water in an increasingly arid West.